FAKTOR-FAKTOR DOMINAN YANG BERPENGARUH TERHADAP PENGUASAAN MATERI PEMBELAJARAN MATEMATIKA GURU SMP DI KABUPATEN INDRAMAYU - Senjaya, Aan Juhana (Universitas Wiralodra, 2017)
This study aims to determine the effect of perception toward math, ability of understand of symbols, mastery of basic concepts, and learning motivation toward the mastery of instructional materials of mathematics. The sample of study consisted of 181 Junior High School math teacher. Data were gathered using questionnaires and tests. Data were analyzed using path analysis with Structural Equation Modeling (SEM). The perception toward math as exogenous variable. The ability of understand of symbols, mastery of math basic concepts, and math learning motivation as exogenous or endogenous variable depend on the path diagram. The endogenous variables is the mastery of mathematics instructional materials. The finding showed that: (a) perception toward math have positive direct effect toward ability of understand of math symbol (β21=0,63); mastery of math basic concepts (β31=50); math learning motivation (β41=0,38); and mastery of math instructional materials (βy1=0,21); (b) ability of understand of math symbol have positive direct effect toward mastery of math basic concepts (β32=0,23); math learning motivation (β42=0,27); and mastery of math instructional materials (βy2=0,35); (c) mastery of math basic concepts have positive direct effect toward math learning motivation (β43=0,26) and to mastery of instructional materials of math (βy3=0,24); the last (d) math learning motivation have positive direct effect toward mastery of math instructional materials (βy4=0,24).